PENGARUH KEMAMPUAN PERSONEL DAN MATERIEL KORPS MARINIR TERHADAP OPERASI PENANGGULANGAN BENCANA - Zainal Zainal; Bambang Dillianto; Juli Herman (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The involvement of elements of the Marine Corps in disaster management operations is to mobilize personnel and materials of the Marine Corps in disaster management operations. In order to improve the quality of resources, personnel and material capabilities are needed to support the main tasks in the context of disaster management. The purpose of this study was to examine the effect of personnel capabilities and material capabilities on the success of the task of disaster management operations for the Marine Corps. The subjects in this study were soldiers of the Marine Corps as many as 127 respondents. The sampling technique uses a non-probability sampling technique where all respondents have the right to be studied. The method used is a quantitative method with data processing using SPSS 25. The results of this study based on hypothesis testing are the t-test of the personnel ability variable of 4.450 while the t-table obtained is 1.661 and the t-test of the material ability variable is 8.946 while the t-table obtained is 1.661. This means that these two variables affect the success of the task of disaster management operations for the Marine Corps. The value of the f test in this study is 65.730, while the f table obtained is 3.091. This means that simultaneously the variables of personnel capabilities and material capabilities affect the success of disaster management operations. The contribution of the two independent variables to the success of the task of disaster management operations for the Marine Corps is 0.578, which means that it is 57.8% and the remaining 42.2% is influenced by other variables.